A systematic review of shoulder injury prevalence, proportion, rate, type, onset, severity, mechanism and risk factors in female artistic gymnasts - Hinds, N.; Angioi, M.; Birn-Jeffery, A.; Twycross-Lewis, R. (Physical Therapy in Sport, 2019)
Objectives: Systematically review shoulder injury prevalence, proportion, rate, type, onset, severity, mechanism, risk factors in female artistic gymnasts. Methods: PubMed, Web of Science, Scopus, Cochrane Library were searched on 7/01/2017. Original studies reporting data for female artistic gymnasts only, of any age or level were included. Quality assessment was undertaken using Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Results: Fifteen observational studies were included. Thirteen were poor/fair quality. Shoulder injury prevalence (0%-86.9%) was higher in international (29.2%) versus national (20%) gymnasts. As a proportion of all injuries, shoulder injuries made up 4.2%-7.5%. Rates (0.35-5.7/1000 athlete exposures) were greater during practice (5.0/1000) than competition (2.4/1000). Multidirectional instability (33.8%, 37.7%) and musculotendinous injury (26.6%-90.9%) were the most common injury. In four studies 66.2%-100% of total shoulder injuries were acute onset. Most (59.3%) shoulder injuries were minor, 7.4% required surgery and 80% caused symptoms post-retirement. Asymmetric bars were the most frequent mechanism of shoulder injury. One study reported excessive shoulder stretching, hyperlaxity and instability as significant (p<0.001) potential risk factors. Conclusions: Shoulder injuries are a problem among female artistic gymnasts. Interventional studies reporting age and competition level-specific data may guide prevention strategy implementation.